AB1004 Sources of Information Used by Patients with Rheumatic Diseases Treated with Subcutaneous Biological Therapy. Rheu-Life Survey. (15th July 2016) - de Toro, F.J.; Batlle, E.; González, C.M.; Cea-Calvo, L.; Pérez-Calvo, M.A.; Carmona, L.
Abstract : Background: Adequate information to patients on disease and therapies is important to improve lifestyle, adherence to treatments and outcomes. Objectives: To describe which are the main sources of information for patients with rheumatic diseases treated with subcutaneous (SC) biological drugs, which ones they consider relevant, and their satisfaction with the information received from the clinical team. Methods: RHEU-LIFE was a survey to patients >18 years with rheumatoid arthritis, axial spondyloarthritis or psoriatic arthritis treated with SC biological drugs, from 50 rheumatology outpatient clinics from Spain. The patients completed the survey anonymously at home. They selected from a list: 1) their sources of general information on disease (multiple choice), 2) the most important (one option), 3) who had informed them about the treatment alternatives (multiple choice) and 4) about the SC biological drug (multiple choice). Results: The survey was given to 1000 patients, 592 responded (59.2%, mean age 51.7 years [SD 13.2], 42.4% men, 57.6% women). The main source of general information on disease was the rheumatologist (92.3%). Other sources mentioned were the primary care physician (21.7%), nurses (19.3%), medical websites (19.8%) or health related blogs (5.6%), brochures for patients (11.5%), friends or relatives (6.3%), patient associations (4.4%) or other patients (3.1%) and pharmacists (3.4%). Information about treatment options and the SC biological drug came mainly from the rheumatologist (>90%) and infrequently from nurses or hospital pharmacists (Table). 46.1% mentioned having received only oral information, 6.0% only written and 45.2% both ways. Some 44.5% and 42.6% reported to be "very satisfied" and "satisfied" with the information received respectively, 10.6% "neither satisfied nor dissatisfied" and 2.1% and 0.2% "dissatisfied" or "very dissatisfied". 45.2% alleged to search for information about the biological treatment in sources other than the hospital clinical staff. Conclusions: The rheumatologist is the main source of information for patients on SC biological drugs. Nurses and hospital pharmacists are seldom mentioned, even though being very often visited for drug dispensing. Satisfaction with the information received is high, however nearly half said to have searched for information on the biological drug in alternative sources. Acknowledgement: This survey was financed by Merck Sharp & Dohme of Spain and endorsed by the patient's association ConArtritis (Arthritis National Coordinator). Disclosure of Interest: None declared